Qui hoạch tuyến giao thông công cộng thí điểm của TP. Đà Nẵng - Bùi, Văn Ca (2011)
Tác giả: Bùi Văn Ca, GS-TSKH; Trần Văn Nam, PGS-TS; Nguyễn Ngọc Diệp, NGUT; Phạm Thị Đông Phương, ThS; Trương Lê Bích Trâm, KS -- Từ khóa: Giao thông công cộng; Giao thông đô thị; Đà Nẵng; Quy hoạch